Penyebab Keterlambatan Konstruksi Proyek Jalan Kota Di Provinsi Sumatera Barat - Ophiyandri, Taufika; Hadiguna, Rika Ampuh; Honesti, Dea (Jurnal Bangunan, Konstruksi & Desain, 2023)
The success of a construction project is determined by the suitability of time, cost and quality specified in the contract documents. However, construction project implementation sometimes experiences delays caused by various factors. Road projects are one of the construction projects that often experience delays in their implementation. Therefore, this research aims to identify the factors that cause delays in the implementation of city road projects in West Sumatra. The research objectives were achieved by conducting a questionnaire survey on 30 respondents who came from owners of the City Road project in West Sumatra who had work experience as Satker, Assistant, KPA, PPK, and PPTK. The data obtained was processed using descriptive statistical analysis. The results of the research show that the factors causing delays that often occur are four factors in the workforce indicator, with the highest frequency being the lack of skills of the workforce involved in road projects.